THE CONTRIBUTION OF COMMUNICATION INTENSITY TO THE RESPONSIBILITY ATTITUDE OF SUPERVISORS IN THE OFFICE OF MINISTRY OF RELIGIOUS AFFAIRS AT MEDAN CITY - Mesiono Mesiono (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
This study aims to determine the magnitude of the contribution of communication intensity in the assignment of the responsibility attitude of the Supervisor at the Ministry of Religious Affairs Office at Medan. Hypothesis proposed; the intensity of communication in the assignment contributed significantly to the attitude of the Supervisory responsibility in the Ministry of Religious affairs Medan. The population of this study is all supervisors in the Ministry of Religious Affairs at Medan. Samples determined by Stratified Proportional Random Sampling Technique, obtained by 30 people. The instrument is designed with questionnaire form for communication intensity variable in assignment and responsibility attitude of Supervisor at Ministry of Religious Affairs at Medan. Two main conditions that must be owned by a data collection tool, they are; validity and reliability. Instrument validity was tested through content validity which was tested to 25 respondents outside the research sample. Instrument reliability was analyzed by Alpha Cronbach. The results of data analysis showed that the intensity of communication in the assignment has a significant contribution to the attitude of the Supervisory Board of Education in the City of Medan for 14.50% with a correlation coefficient of 0.381